Room‐Temperature, High‐SNR Upconversion Spectrometer in the 6–12 µm Region. Issue 3 (1st February 2021) - Rodrigo, Peter John; Høgstedt, Lasse; Friis, Søren Michael Mørk; Lindvold, Lars René; Tidemand‐Lichtenberg, Peter; Pedersen, Christian
Abstract: Mid‐infrared (MIR) spectroscopy, which has important applications in medicine, environmental monitoring, materials, and food science, is widely performed using Fourier transform infrared (FTIR) spectrometers as gold standard. Despite decades of development, FTIR systems are vulnerable to vibration and have limited temporal resolution due to reliance on mechanically scanned mirrors and MIR direct detectors that have a slower response than their near‐infrared counterparts. Using cryogenically cooled detectors, state‐of‐the‐art FTIR systems have reached a signal‐to‐noise ratio (SNR) of ≈6000 at 1 s integration time (at 4 cm −1 spectral resolution). Here, a novel MIR upconversion spectrometer (MIRUS) is presented with a record‐high SNR > 10 000 at 1 s (6 cm −1 resolution), outperforming FTIR systems by circumventing the need for sophisticated cooling and any moving part, thus enabling operation in harsh environments. It has a spectral coverage of 6–12 µm—the broadest for an upconversion spectrometer to date. The MIRUS uses broadband intracavity upconversion to convert the signal spanning the MIR fingerprint region to the near‐infrared where sensitive Si‐detector based spectrometers operate with rates easily reaching kilo spectra per second. Applications of MIRUS for gas sensing, plastic identification, and rapid photopolymerization monitoring are demonstrated. Abstract : A mid‐infrared upconversion spectrometer (MIRUS) with no cryogenically cooled detector or any moving part is presented. MIRUS operates in the highly relevant 6–12 µm fingerprint region. Combining these attractive features with its high signal‐to‐noise ratio >10 000 at 6 cm −1 resolution and 1 s integration time, MIRUS offers an alternative to Fourier transform infrared spectrometers extensively used in MIR spectroscopy.